In vitro皮膚透過性を指標としたモデル軟膏処方の最適化 - 矢野, 耕也; 竹田, 秀一; 中川, 喬; 淺原, 初木; 太田, 裕一郎 (品質工学, 1998)
In　this　study,　quality　engineering　(Taguchi　Methods)　was　applied　to　the　formulation　of　an ointment.　ln　order　to　obtain　good　ointment　permeability　through　skin,　the　"in　vitro" permeability　was　measured　as　the　duality　characteristic.　The　excised　skins　from　rats　and micro-pigs　were　used　in　the　permeation　test. All　ingredients　in　the　model　ointment　were　selected　as　control　factors　and　assigned　to　an　L18 orthogonal　array.　Animal　species　were　considered　as　the　noise　factor　conditions　so　that　the optimum　condition　would　be　robust　against　species.　For　the　generic　function,　it　was considered　that　the　cumulative　amount　of　penetration　should　be　proportional　to　time.　Zero point　proportional　equation,　Y=　βT　was　used,　where　Y,　β　and　T　denote　the　cumulative　drug penetration　per　uniｔ, constant,　and　time　respectively. As　a　result,　excellent　permeability　was　obtained　under　the　optimum　condition　with　little dependency　on　different　species.　Such　success　was　accomplished　with　a　single　repetition　in the　test,　in　contrast　to　traditional　testing　with　many　repetitions　in　animal　experimentation.